Fuel Ratio (liter/bcm) Reduction Through Fleet Management Optimization in Open Pit Coal Mining at PT. KPC - Ramli, Denastri; Simatupang, Togar M (The Indonesian Journal of Business Administration, 2015)
Abstract. On Pit Bendili Truck is the most contribution of Total fuel consumption. Its about 72 % of the total consumption. This Research focus on decreasing delays Trucks occurred when unproductive engine running and increase productivity Shovel especially on R9800B that actual productivity (2900 bcm/hr) is under plan (3100 bcm/hr). Queuing Truck is the most unproductive delay in Pit Bendili. Cycle time Truck depends on loading point and dumping point. It is a fix plan from Team Techincal, on this research is not focus on cycle time. Man and Method on operation are other factors that influencing of fuel ratio. The goal of the thesis is find dominant factor and give recommendation to production team in order to reduce fuel ratio until 3,19% from fuel ratio 1.43 ltr/bcm to 1.38 liter/bcm. And potential of cost saving from fuel consumption isÂ US $ 748,985 from May to December 2015.Key words : Fuel Ratio, Shovel, Delay unproductive truck, Queuing, Shovel Productivity, overburden removedÂ